Evil in contemporary French and Francophone literature - Powers, Scott M. (Cambridge Scholars Pub., 2011)
Evil remains a primary source of inquiry in contemporary literature of French expression, even among its most secular writers. In considering French-speaking authors from France, Belgium, the United States, the Maghreb, and Sub-Saharan Africa, this collection delineates a rich international perspective on some of the most disturbing events of our time. Each essay testifies to the urgency expressed in works of fiction to give an account of human catastrophes, from the Shoah and the Rwandan gen ...